2009
DOI: 10.1111/j.1440-172x.2009.01733.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and treatment satisfaction in the context of diabetes self‐management education

Abstract: The aim of this study is to identify and compare factors affecting quality of life and treatment satisfaction in people attending the structured educational programme for patients with intensified insulin therapy. A sample of 104 patients was recruited from diabetes specialized centre between November 2006 and March 2007. For measure patient's quality of life, the Audit Diabetes Dependent Quality of Life questionnaire and for measure patient's satisfaction with their treatment regimen, the Diabetes Treatment S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
3
12
1
Order By: Relevance
“…We did not find any study similar to ours; thus, we are unable to discuss this association between treatment satisfaction and HRQoL in the light of other results. However, studies performed among different populations such as diabetic patients have linked low correlation between treatment satisfaction and HRQoL . The modest positive correlation between treatment satisfaction and HRQoL found in our study seems to be consistent with previous published research which indicated that treatment satisfaction and HRQoL are two fairly distinct phenomena .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We did not find any study similar to ours; thus, we are unable to discuss this association between treatment satisfaction and HRQoL in the light of other results. However, studies performed among different populations such as diabetic patients have linked low correlation between treatment satisfaction and HRQoL . The modest positive correlation between treatment satisfaction and HRQoL found in our study seems to be consistent with previous published research which indicated that treatment satisfaction and HRQoL are two fairly distinct phenomena .…”
Section: Discussionsupporting
confidence: 92%
“…We did not find any study similar to ours; thus, we are unable to discuss this association between treatment satisfaction and socio‐demographic and clinical characteristics of hypertensive patients in the light of other results. However, studies performed among different populations such as diabetic patients have linked a correlation between treatment satisfaction and socio‐demographic or clinical factors . The present findings seem to be consistent with other research which found that demographic parameters (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Respondents diagnosed for more than ten years reported lower QoL scores than patients diagnosed for a shorter period. In the literature, the association between duration of diabetes and QoL is mixed, with studies finding that increased duration of diabetes was associated with decreased QoL [9,28,35], while others found no association [36]. As previously shown [29], the presence of complications was associated with lower PCS and QoL, but neuropathy, retinopathy and cardiovascular disease were the three complications that remained in the final multivariate model for QoL, suggesting that they are the strongest factors associated with poor QoL.…”
Section: Discussionmentioning
confidence: 92%
“…Gurkova et al . found that participants with type 2 diabetes treated with IIT reported a greater negative impact on QOL than did subjects with type 1 diabetes [28].…”
Section: Discussionmentioning
confidence: 92%